Acaulospora fanjing (Glomeromycota), a new species of arbuscular mycorrhizal fungi from Fanjingshan in China - He, Rong-Jian; Long, Chun-Li; Yao, Li-Mei; Jiang, Long (Phytotaxa, 2021)
Acaulospora fanjing is here described as a new species of arbuscular mycorrhizal fungi (AMF; Glomeromycota) based on morphological and phylogenetic analyses. It was associated with roots of Acer flabellatum colonizing of the massy dwarf forest to fanjing Mountain, China, and this is the only site of its occurrence known to date. A.fanjing is characterized by forming reddish orange to reddish brown globose spores of (109–)123(–138) µm diam and three layers of outer spore walls (SWL1–SWL3) and two layers of germinal walls (MW and IW). SWL1 hyaline, short–lived, evanescent, SWL2 laminate, orange to reddish orange, 2.0–3.5 μm thick and SWL3 thin, difficult to observe; MW is hyaline, bilayered (MWL1–MWL2), semiflexible; IW is hyaline, with three layers and not “beaded” structure, only the IWL2 were stained light pink in Melzer’s reagent. A.fanjing can be distinguished from all other Acaulospora species by spore size, color and spore wall structure. Phylogenetic analysis based on the AMF extended DNA barcode covering a 1.5-kb fragment of the small subunit (SSU), internal transcribed spacer region (ITS), and the large subunit (LSU) of rRNA genes places A.fanjing in the genus Acaulospora, separated from other described Acaulospora species. All available sequences in public databases suggest that this new fungal species has not yet been previously detected.